Soil fertility and nutritional status of 'Ponkan' mandarin under solid organic residues and chemical fertilization - Santos, Carlos H.; Filho, Hélio Grassi [UNESP]; Santos, Jacqueline C. [UNESP]; Penteado, Bruna B. [UNESP] (FapUNIFESP (SciELO), 2011)
The objective of this research was to evaluate some soil chemical attributes and the nutritional status of 'Ponkan' mandarin managed with organic residues and chemical fertilization. The experiment was carried out at the Natural Resource Department - Soil Science Area, in the College of Agronomic Sciences - UNESP/Botucatu, SP. 'Ponkan' Mandarin seedlings were cropped and managed using the organic residues sewage sludge, cattle manure and chemical fertilization. The results allow the conclusion that there was an increase in the CEC, OM, N-total, P and K values in the soil managed with organic residues. The sewage sludge application did not harm the soil quality because the input of elements As, Cd, Cr and Hg present in its constitution were not significant. The soil management with organic residues increased significantly contents of N, P, Ca and S in 'Ponkan' leaves but did not contribute to increase significantly the elements B, Cu, Fe, Mn, Zn, As, Cd, Cr and Pb. The soil management with sewage sludge did not result in significant increase in the As, Cd, Cr and Hg content of leaves and fruits.
Fertilidade do solo e nutrição de tangerineiras 'Ponkan' manejados com resíduos sólidos e adubação química
Keywords: Mineral nutrition; Mineralization; Organic matter; Sewage sludge